Harry Potter and the philosopher's stone - Rowling, J. K. (Bloomsbury, 2014)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Witchcraft and Wizardry.